Peran Santri dalam Pelestarian Lingkungan - Wenny Kania Aprilia; Saeful Anwar; Dedi Herdiana (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
The purpose of this study was to find out more about the role of students in environmental preservation especially students in the Qira’atussab’ah Islamic Boarding School of the Kudang to know the processes of activities that take place in preserving the environment and the results obtained by the students of the cottage Qira’atussab’ah Islamic Boarding School of the Kudang. The research method used is descriptive method with a qualitative approach. The results of the study revealed that the pondok pesantren environmental preservation program’s main objective is to realize students who have awareness in behaving environmentally friendly so that ecosystem sustainability is maintained. Concrete steps taken by students in preserving the environment with activities that have become students habits include cleaning kobong, cleaning kyai houses environment of boarding school. The results obtained are increased awareness of students in preserving the environment.